Determination of Frequently Used Parabens in Shampoo and Conditioners using Validated HPLC Assay Method - Lavakumar, S.; Vivekanand, P.A.; Prince, A.A.M. (Asian Journal of Chemistry, 2021)
Parabens are esters of p-hydroxy benzoic acid and widely used as preservatives with a broad spectrum of antimicrobial activity in cosmetic, foods and pharmaceutical products. Methyl, ethyl, propyl and butyl paraben are commonly used in many cosmetic products. The concentration level of these parabens was restricted to maximum 1%. Recently, many cosmetic products such as shampoo and hair conditioners are available in the Indian market with label claims "no-parabens in the products". A HPLC method is developed for determining four frequently used parabens namely, methyl, ethyl, propyl and butyl paraben in shampoo and hair conditioners. The chromatographic separation was carried out on Phenomenex Kromasil C18 column (150 mm × 4.6 mm i.d, 5 μm particle size) with water: methanol (60:40 v/v) as mobile phase and UV detection was performed at 254 nm. The method was validated with respect to specificity, linearity, accuracy, precision and robustness. The calibration curve was achieved to be linear and regression coefficient obtained was > 0.9999 for all the parabens. Accuracy of chromatographic method was evaluated by standard addition method; paraben content was estimated in eleven commercial shampoos and four hair conditioners available in Indian market which were claimed as no parabens were evaluated to assess the quality of claims of these samples. The results indicated that all the tested shampoos and hair conditioners met the requirements of the standards.